Application of Golden Sine Algorithm in Hydrogeological Parameter Optimization - ZHOU Yourong; LI Na; ZHOU Fahui (Renmin Zhujiang)
To improve the accuracy of hydrogeological parameters, this paper conducts the simulationverification of golden sine algorithm (Gold-SA) algorithm by six standard test functions andcompares the simulation results with that of the particle swarm optimization (PSO) algorithm, andtaking two pumping test data as examples, optimizes two key parameters, i.e. transmissivitycoefficient and storage coefficient of theis formula by the Gold-SA algorithm and compares theresults with that of the PSO algorithm, wiring method and literature method. The results show thatthe Gold-SA algorithm has better optimization accuracy for the six selected standard testfunctions than the PSO algorithm, with better optimization accuracy and global search ability. Andthe optimization accuracy of Gold-SA algorithm for the transmissivity coefficient and storagecoefficient of the two examples is better than PSO algorithm, wiring method and literature method.Therefore, it is feasible and effective to apply the Gold-SA algorithm for the optimization ofhydrogeological parameters.